Révision du corpus des marques de potiers sur les sigillées italiques découvertes en Algérie : nouvel apport de données - Brahim Boussadia (Antiquités Africaines, 2018)
The sorting on a batch of stamps on italic sigillata from an old collection of the Service des Monuments historiques de l’Algérie, made it possible to release four unpublished stamps, including two, belonging to the potters APOL(L)ONIVS and M. TVLIVS, make their entry in the corpus of the marks of potters on terra sigillata; these stamps are among the rare ones of these potters unearthed in the Maghreb. This contribution also makes it possible to focus, with the proliferation of production workshops, on the importance of chemical and petrographic analyses in determining the origins of production and distribution channels.